OP0062-HPR Efficacy of Tailored Exercise Therapy in Patients with Knee Osteoarthritis and Comorbidity: A Randomized Controlled Trial. (15th July 2016) - De Rooij, M.; van der Leeden, M.; Cheung, J.; van der Esch, M.; Arja Häkkinen, A.; Haverkamp, D.; Roorda, L.D.; Twisk, J.; Vollebregt, J.; Lems, W.F.; Dekker, J.
Abstract : Background: Exercise therapy is a key intervention in the management of knee osteoarthritis (OA). It is an effective intervention to improve physical functioning and reduce joint pain in patients with knee OA. Comorbidity, which is highly prevalent in OA, interferes with the application of exercise therapy and contributes to non-adherence to exercise therapy. Objectives: To evaluate the efficacy and safety of tailored exercise therapy on physical functioning in patients with knee osteoarthritis (OA) and comorbidity Methods: A randomized clinical controlled trial was performed, comparing comorbidity-adapted exercise therapy with a control intervention. The study was conducted in an outpatient rehabilitation center. Patients with a clinical diagnosis of knee OA and at least one of the target comorbidities, i.e., coronary disease, heart failure, type 2 diabetes, COPD or obesity (body mass index≥30kg/m) with severity scores ≥2 on the Cumulative Illness Rating Scale were included. The intervention group received a 20 weeks individualized, comorbidity-adapted exercise program, with 2 sessions of 30 -60 minutes a week. Participants in the control group received their current medical care for knee OA and were placed on a waiting-list for exercise therapy. Measurements were performed at baseline, at 10-weeks, 20-weeks (post-treatment) and 32 weeks (3-months post-treatment). Primary outcome measures: physical functioning (WOMAC subscale physical functioning and six minute walking test). Generalized Estimating Equation analysis was used to estimate group differences over time, adjusting for baseline value of outcome measure. Results: In total, 126 participants were randomised, of which 63 participants in the experimental group and 63 in the control group. Statistically significant differences were found over time between the intervention and control group with respect to physical functioning WOMAC-pf and the six minute walk test in favour of the intervention group. The improvements in the experimental group were clinically relevant. The mean improvements in the intervention group on physical functioning were 33% on the WOMAC-pf scale and 15% on the six-MWT at 3 months follow up. No serious adverse events occurred during the intervention. Conclusions: This is the first study showing that tailored exercise therapy is safe and effective in improving physical functioning, in patients with knee OA and comorbidities. These results should encourage clinicians to consider exercise therapy as a treatment option for patients with knee OA, even in the presence of comorbidity. Disclosure of Interest: None declared